UJI AKTIVITAS ANTI BAKTERI LARUTAN DISINFEKTAN ALAMI INFUSA DAUN SIRIH (Piper Betle L.) TERHADAP Staphylococcus aureus - Nori Wirahmi; Muhammad Ichsan Triansyah; Zul Amri; Camelia Putri Masrijal (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
This study is a test of the anti-bacterial activity of natural disinfectant solution of betel leaf infusion (Piper Betle L.) against staphylococcus aureus. This study aims to determine the anti-bacterial activity of betel leaf infusion disinfectant solution against staphylococcus aureus. This study used the disc diffusion method by looking at the inhibition area in the presence of a clear area around the disc. The betel leaf infusion concentration used was 60% w/v and 90% w/v. The analysis used is descriptive analysis. The results of this study indicate that betel leaf infusion with a concentration of 90% w/v is better than betel leaf infusion with a concentration of 60% w/v. Betel leaf infusion concentrated 90% w/v had an inhibition area of ​​6.66 mm and betel leaf infusion concentrated 60% w/v had an inhibition area of ​​2.13 mm. The 90% w/v concentration of betel leaf infusion is included in the moderate anti-bacterial category and 60% w/v concentrated betel leaf infusion is in the weak category. Betel leaf infusion can be used as a natural disinfectant and is safe to use.